2012
DOI: 10.1590/s1413-70542012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and total antioxidant capacity of cashew apples (Anacardium occidentale L.) during the ripening of early dwarf cashew clones

Abstract: Lately, tropical fruit consumption has increased due to a higher knowledge of its nutritional and therapeutic value. The aim of this work was to evaluate the antioxidant potential of cashew apples from different early dwarf clones during their ripening. The clones analyzed included: CCP 76, CCP 09, BRS 189 and BRS 265 in seven ripening stages. They were analyzed for vitamin C, total carotenoid, total anthocyanin, yellow flavonoids and polyphenol content and total antioxidant capacity. Clone BRS 265 ripe cashew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
4
33
1
6
Order By: Relevance
“…But it is possible to correlate the antioxidant activity described with extraction of total phenols and tannins, highlighting the importance of these bioactive compounds inthe antioxidant capacity of these extracts studied. These results corroborate those obtained by Lopes et al (2012), who found a positive correlation between the amount of phenolics and antioxidant activity.…”
Section: Resultssupporting
confidence: 92%
“…But it is possible to correlate the antioxidant activity described with extraction of total phenols and tannins, highlighting the importance of these bioactive compounds inthe antioxidant capacity of these extracts studied. These results corroborate those obtained by Lopes et al (2012), who found a positive correlation between the amount of phenolics and antioxidant activity.…”
Section: Resultssupporting
confidence: 92%
“…In a screening of 15 olive tree clones, some were found to have high total polyphenol, oleic and linoleic acid contents [33]. The vitamin C, total carotenoid, total anthocyanin, yellow flavonoids and polyphenol contents and total antioxidant capacity were analyzed in clones of cashew apples, and differences were found between clones [34,35]. Dietary fiber and phenolic compounds were also found to be high in selected clones of acerola and cashew apple [36].…”
Section: Methods For Improving Plant Phenolic Contentmentioning
confidence: 99%
“…BRS 366 and Florida Sweet showed contrasting behavior regarding their sugar (Table 1) and vitamin C contents; as the one with highest vitamin level accumulated less sugar ('BRS 366') and the one with the sweetest fruits had a lower vitamin C concentration ('Florida Sweet'). Despite the observed decline, the evaluated acerola varieties still presented high vitamin C contents compared to other fruits as orange, guava and cashew apple with 62.50, 135.70 and 279.37 mg.100 g -1 , respectively (COUTO; CANNIATTI-BRAZACA, 2010;SILVA et al, 2010;LOPES et al, 2012).…”
Section: Quality and Non-enzymatic Antioxidantsmentioning
confidence: 98%